DASHBOARD SALES PERFORMANCE DAN SALES SUMMARY REPORT TABLE SADATA.ID - Febrian Valentino Agape; Gst Ayu Vida Mastrika Giri; I Made Widhi Wirawan (Jurnal Pengabdian Informatika, 2026)
In a competitive digital era, effective sales data management is essential to support business strategies that are responsive to market changes. Implementing interactive and informative data visualization technology is a significant step in helping companies gain comprehensive insights into their sales performance. This study documents the development and evaluation of the Sales Performance Dashboard and Sales Summary Report Table at SADATA.ID as a tool to enhance the efficiency of sales analysis. The dashboard integrates key metrics, including brand and category performance through monthly trend graphs, and provides distributor and employee data summaries to strengthen long-term performance visibility. Through a comprehensive approach, from user needs analysis to system testing, this dashboard is designed to meet the company's need for faster, more accurate, and easily interpretable data access. The results show that the system effectively provides users with an intuitive interface for monitoring sales performance and supports data-driven business decisions. This research is expected to contribute to the development of sales data analytics technology focused on enhancing operational efficiency and effectiveness in companies.